Phosphorylated Tau 181 Serum Levels Predict Alzheimer’s Disease in the Preclinical Stage - Qin, Wei; Li, Fangyu; Jia, Longfei; Wang, Qi; Li, Ying; Wei, Yiping; Li, Yan; Jin, Hongmei; Jia, Jianping (Frontiers in Aging Neuroscience, 2022)
Background: There is an urgent need for cost-effective, easy-to-measure biomarkers to identify subjects who will develop Alzheimer’s disease (AD) especially at the pre-symptomatic stage. This stage can be determined in autosomal dominant AD (ADAD) who offers the opportunity to observe the dynamic biomarker changes during the life-course of AD stages. This study aimed to investigate serum biomarkers during different AD stages and potential novel protein biomarkers of presymptomatic AD. Methods: In the first stage, 32 individuals (20 mutation carriers including 10 with AD, and 10 with mild cognitive impairment (MCI), and 12 healthy controls) from ADAD families were analyzed. All subjects underwent a complete clinical evaluation and a comprehensive neuropsychological battery. Serum samples were collected from all subjects, and antibody arrays were used to analyze 170 proteins in these samples. The most promising biomarkers were identified during this screening and were then measured in serum samples of 12 subjects with pre-MCI and 20 controls. Results: The serum levels of 13 proteins were significantly different in patients with AD or MCI compared to controls. Of the thirteen proteins, cathepsin D, immunoglobulin E (IgE), epidermal growth factor receptor (EGFR), matrix metalloproteinase-9 (MMP-9), von Willebrand factor (vWF), haptoglobin, and phosphorylated Tau-181 (p-Tau181) correlated with all cognitive measures (R2=-0.69–0.76). The areas under the receiver operating characteristic curve of these seven proteins were 0.71–0.93 for the classification of AD and 0.57–0.95 for the classification of MCI. Higher levels of p-Tau181 were found in the serum of pre-MCI subjects than in the serum of controls. The p-Tau181 serum level might detect AD before symptoms occur (area under the curve 0.85, sensitivity 75%, specificity 81.67%). Conclusions: A total of 13 serum proteins showed significant differences between subjects with AD and MCI and healthy controls. The p-Tau181 serum level might be a broadly available and cost-effective biomarker to identify individuals with preclinical AD and assess the severity of AD.